IMPLEMENTATION OF GROUP DEFINITION OF FUNCTIONAL SECURITY PROFILE AND LEVEL OF GUARANTEES OF THE INFORMATION AND TELECOMMUNICATION SYSTEM FROM UNAUTHORIZED ACCESS (Information systems and technologies security, 2024)
The article proposes, shows and analyzes the main stages ofimplementing software for group assessment of a functional profile anddetermining or agreeing the level of guarantees for the correct implementation offunctional security services in information security tools of information oftelecommunication systems from unauthorized access in Ukraine based ontheoretical studies previously conducted. The necessary regulatory documents ontechnical protection of information governing the procedure of evaluating anddetermining the level of guarantees of automated systems against unauthorizedaccess in Ukraine are covered. The program was designed using the Data FlowDiagram, namely, a contextual diagram of the group definition process and adecomposed diagram of the process of group determination of the functionalsecurity profiles and the level of guarantees. More detailed flowcharts ofsoftware and algorithms are constructed. A prototype of the software isimplemented; examples of work on each of the main blocks of work that were previouslydesigned in the diagrams and flowcharts of the algorithms are given.Certain advantages and disadvantages of the developed software for groupdetermination of the functional security profile and the level of guarantees aredefined. The developed program allows to carry out group estimation and tocompare the results sent to the server. This approach reduces the time spent bythe security administrator to determine the security profiles and security levels ofthe information being processed against unauthorized access and to detectwhether a specified functional profile coincides with a standard one (providedthis match the user is provided with information about that standard functionalprofile) or determine another level of warranty. By conducting a groupexamination, the reliability of the obtained results increases.
Keywords: information and telecommunication system automated system; information security; functional security profile; level of guarantees; information security policy; rules of access delimitation; unauthorized access; a set of security features; expert information